Jona: Die rekonstruksie van "n karakter - Barkhuizen, J. H. (Hervormde teologiese studies, 1988)
Jonah: The reconstruction of a character The purpose of this article is twofold: (i) first to present a useful model of characterization postulated by De Beus, expanded by Brink, and, on narratological grounds, corrected by the present author; (ii) this model is accordingly applied to reconstruct the character of Jonah in the Septuagint version of this Biblical narrative.